2018
DOI: 10.1039/c8nr04048f
|View full text |Cite
|
Sign up to set email alerts
|

Codelivery of a cytotoxin and photosensitiserviaa liposomal nanocarrier: a novel strategy for light-triggered cytosolic release

Abstract: Light-triggered intracellular delivery of a protein toxin was achieved by codelivery via a liposomal nanocarrier, targeted with a cell-penetrating peptide (CPP)–photosensitiser conjugate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 62 publications
0
18
0
Order By: Relevance
“…PCI is a light-based method and is employed to trigger the endosomal escape of RIP. Saporin linked with a photosensitizer functionalized CPP showed cytotoxicity augmentation in MC28 fibrosarcoma cells [135]. Another study also showed that the cytotoxicity of IT 225.28-saporin was strengthened by using PCI with a photosensitizer disulfonated tetraphenyl chlorin (TPCS2a) [136].…”
Section: Perspectivesmentioning
confidence: 98%
“…PCI is a light-based method and is employed to trigger the endosomal escape of RIP. Saporin linked with a photosensitizer functionalized CPP showed cytotoxicity augmentation in MC28 fibrosarcoma cells [135]. Another study also showed that the cytotoxicity of IT 225.28-saporin was strengthened by using PCI with a photosensitizer disulfonated tetraphenyl chlorin (TPCS2a) [136].…”
Section: Perspectivesmentioning
confidence: 98%
“…Another approach to nanocarrier-assisted PCI was presented by Yaghini et al [148], where the authors used liposomes surface-functionalised with a cell penetrating peptide (CPP). The CPP had additionally a porphyrin moiety (meso-tetrakis tetraphenylporphyrin (TPP)-derivative) as the PS, conjugated to its N-terminus.…”
Section: Nanoparticle-mediated Pci As a Powerful Anticancer Drug Delimentioning
confidence: 99%
“…The drug delivery systems, both passively and actively, triggering the endolysosomal escape of the encapsulated substances have been developed in various studies with different mechanisms; for example, pH buffering/proton sponge, [5][6][7] osmotic pressure shock, 8 the flip-flop approach, 9 and photochemical/photophysical internalization. 10 The photochemical/photophysical internalization is defined by the incorporation of a photosensitive moiety into a carrier, and letting cargoes flee from the endolysosomes upon lightactivated chemical reactions and/or physical alterations. This light-triggering mechanism is spatially and time controllable.…”
Section: Introductionmentioning
confidence: 99%